The Image of Chinese Art of the Ming Dynasty in the Spanish Context in the Exhibition "Art and Culture around 1492" - Jiayi, Liu (Sinología hispánica. China Studies Review, 2024)
To commemorate the 500th anniversary of Columbus' discovery of the American New World, the Seville Expo’ 92 held an exhibition entitled "Art and Culture about 1492", which presented 15th century artworks from all over the world. This essay will analyze the exhibition's background, purpose, data on the works exhibited, and the theme of the exhibition, combining statistical and image analysis methods, and then investigate the absence of the image of Chinese Ming art generated by the exhibition's discourse. By comparing the literature on the history of Chinese Ming art with the works in the exhibition, it is clear that the image of Chinese art constructed by the exhibition actually lacks individual art forms that were painted with fine brushwork, such as Yuanti paintings, folk wall paintings and woodcut prints. These paintings, however, actually occupied an important status in the artistic landscape of the Ming dynasty. It is hoped that this study will help to establish and correct the absence and deficiencies in the identity of Chinese Ming art constructed by the exhibition in the Spanish context.